The Impact of World War II on the Demand for Female Workers in Manufacturing. (29th June 2018) - Shatnawi, Dina; Fishback, Price
Abstract : Most studies of female workers in the 1940s focus on labor supply. We use the basics of supply and demand to measure the impact of WWII on the short- and medium-run demand for female workers in manufacturing. Demand rose for both salaried and production female workers during the war and then fell after the war. However, the post-war demands for both groups were substantially higher than before the war and higher than the levels that would have been reached had the demands followed a counterfactual growth path from the boom period in the 1920s.